The equation of the circle can be written in standard form and in a general form
The center of the circle is (-4,6) and the radius is [tex]\sqrt{23[/tex]
The equation of the circle is given as:
[tex]x^2 + 8x + y^2 - 12y = -29[/tex]
Rewrite as:
[tex]x^2 + 8x + k - k + y^2 - 12y + k - k= -29[/tex]
Express k as the square of the half of the coefficients of x and y.
So, we have:
[tex]x^2 + 8x + (4)^2 - (4)^2 + y^2 - 12y + (6)^2 - (6)^2= -29[/tex]
Evaluate the exponents
[tex]x^2 + 8x + 16 - 16 + y^2 - 12y + 36 - 36 = -29[/tex]
Collect like terms
[tex]x^2 + 8x + 16 + y^2 - 12y + 36 = -29 + 16 + 36[/tex]
Express as perfect squares
[tex](x + 4)^2 + (y - 6)^2 = -29 + 16 + 36[/tex]
[tex](x + 4)^2 + (y - 6)^2 = 23[/tex]
The standard equation of a circle is:
[tex](x - a)^2 + (y - b)^2 + r^2[/tex]
Where:
Center = (a,b)
Radius = r
So, we have:
Center = (-4,6)
Radius = [tex]\sqrt{23[/tex]
Hence, the center of the circle is (-4,6) and the radius is [tex]\sqrt{23[/tex]
Read more about circle equation at:
https://brainly.com/question/1559324